Hubungan Antara Kekuatan Genggaman, Koordinasi Mata-Tangan Dan Percaya Diri Dengan Ketepatan Service - Hari Bowo, Yudha Ranto (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2016)
The accuracy means the right or hit the target. The accuracy is meant here is an attempt to control the direction of service in accordance with the objectives to be achieved. To embarrass an opponent in his quest to return the ball from the blow service, do not let your opponent guessing and knowing where the ball will fall in room service. This research is a correlation between several variables conducted on students who attend a few games of tennis. The results of the data analysis of the relationship between grip strength (X1), eye-hand coordination (X2) and confidence (X3) with accuracy of service (Y) has Rx123y correlation coefficient = 0.897 and F count = 21.957 stating the level of relationship between grip strength, coordination eyes hand and confident with the accuracy of the service is very high.